2009
DOI: 10.1080/02786820903124698
|View full text |Cite
|
Sign up to set email alerts
|

A Temperature Calibration Procedure for the Sunset Laboratory Carbon Aerosol Analysis Lab Instrument

Abstract: The Sunset Laboratory Carbon Aerosol Analysis Lab Instrument is widely used for thermal-optical analysis (TOA) of ambient particulate matter samples to measure total carbon (TC), organic carbon (OC), and elemental carbon (EC), and often thermal subfractions of OC and EC. TOA operating protocols include a series of plateau temperatures at which the thermal sub-fractions evolve. The temperatures have conventionally been measured by a sensor located in the sample oven but away from the filter sample. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 11 publications
4
23
0
Order By: Relevance
“…The classification of OC and EC is widely acknowledged, but their boundary is still not clear and highly operationaldependent (Schmid et al, 2001;Pöschl, 2005). Among the commonly accepted OC/EC determination methods, the thermal-optical analysis (TOA) method is one of the most well-known techniques (Schmid et al, 2001;Chow et al, 2004;Phuah et al, 2009;Cavalli et al, 2010). It typically begins with a heating step in an inert (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The classification of OC and EC is widely acknowledged, but their boundary is still not clear and highly operationaldependent (Schmid et al, 2001;Pöschl, 2005). Among the commonly accepted OC/EC determination methods, the thermal-optical analysis (TOA) method is one of the most well-known techniques (Schmid et al, 2001;Chow et al, 2004;Phuah et al, 2009;Cavalli et al, 2010). It typically begins with a heating step in an inert (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Seventeen different laboratories equipped with similar instrumentation followed similar calibration procedures, including those for temperature (Phuah et al, 2009). For EC, the standard deviation among laboratories was 25.5% for the NIOSH870 and 19.5% for the EUSSAR2 protocols.…”
Section: Panteliadis Et Al's (2014) Recent Interlaboratory Comparisomentioning
confidence: 99%
“…In addition, Tempilaq ‱ G can only be tested at temperatures for which the calibration liquids are available, not at real operating filter temperatures. More recently, Phuah et al (2009) confirmed the oven-filter temperature discrepancy on four different Sunset Laboratory instruments and reported statistically insignificant differences for the IMPROVE total carbon (TC), OC, and EC concentrations after temperature calibration. The calibration method developed in that study involved a simple hardware change by way of a temperature probe introduction that did not harm the instrument.…”
Section: Introductionmentioning
confidence: 83%
“…A temperature bias of up to 50 ‱ C was observed, but did not influence the OC and EC concentrations measured with the IMPROVE protocol. Limitations of the temperature calibration method for the DRI analyzer include use of temperature-indicating (Tempilaq ‱ G, Tempil Inc., South Plainfield, NJ, USA) liquids that damage the quartz surfaces of the sample holder and oven, poison the oxidation catalyst, and contaminate downstream components, as noted in Phuah et al (2009). In addition, Tempilaq ‱ G can only be tested at temperatures for which the calibration liquids are available, not at real operating filter temperatures.…”
Section: Introductionmentioning
confidence: 99%